Rhetorical elements used for marketing post on Instagram by Malaysian local cosmetic product: a study of multimodal discourse analysis - Syed Khalid, Sharifah Syazwa Amierah; Abd Rahman, Amir Lukman; Amir Yazid, Amirah Athirah; Mohammad Omar, Nur Diana Nabila (UiTM Cawangan Johor, 2022)
This study focuses on the rhetorical elements that are used for marketing posts on Instagram by a Malaysian local cosmetic product through multimodal discourse analysis. This study mainly revolves around social media as it deals with various technicalities including images, texts, nonverbal and colors. The three main characteristics of rhetorical elements named logos, ethos, and pathos are studied by analysing posts by the company as an act of persuasion for their audience. This paper adopted Kennedy's (2006) Visual Rhetorical Elements Framework rhetorical elements (logos, ethos, and pathos) as the focal point of the research in analysing Nita Cosmetics ' social media page. 30 posts were selected from Nita Cosmetics ' Instagram page and these posts were analysed. The rhetorical elements in this study would be logos which shows objective truth and portray the quality of the source, the element of ethos represents logic and character which conveys the element of "need and wants " and dependability to the consumers, while pathos reflects around emphasis and engagement. From the findings, it shows that all these elements were used by Nita Cosmetics which enabled them to persuade, attract and engage with their consumers to stay relevant in the business.